Trust during times of the financial crisis in German SME collaborations - Köster, Hans (2012)
While research on collaboration emphasises its rising importance, research broadly overlooked the role of SMEs within todays supply chains and thus in collaborations. Especially the role of trust within collaborative relationships in SMEs has been left out. Furthermore, little research on collaboration and trust in times of crisis has been published. Due to the rising importance of SMEs in the business world, this research concentrates on collaboration within SMEs during the financial crisis and investigates the role of trust within such relationships. This research uncovers the active measure taken by SMEs to create corporate trust and discovers the importance of trust in the absence of power in SC partnerships. Additionally, the impact of SME networks is described including the benefits arising from the participation in such a network. The results on trust and collaboration within crisis situation show the importance of competency, trust and acting according to business rules. For gaining information, a case study approach was chosen. Interviews with owners, managing directors and personnel in leading positions within five German SMEs were carried out. All case companies have been hit severely during the financial crisis with revenue drops of 40% to 50% in 2009.